E-Governance and Privacy: Analyzing the Privacy Implications of Digital Government Initiatives in India - Dalal, Priyanka; Richa (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
In the advent of considerable technology development and the increasing penetration of digital platforms, e-governance projects have been integrated by governments across the globe to transform the delivery of public services and improve citizen engagement. India has been viewed as a notable mover in the digital government sector, and it has a variety of projects designed to enhance the effectiveness of government and inclusion in the digital space. This paper explores the vast field of e-governance in India and the privacy issues raised by the country's adoption of electronic technology. Acquisition, retention, and utilization of citizen data have become critical to setting the standards in digital governance. These elements are central to delivering personalized services to individuals and improving back-end processes. Some essential focus areas are data management, regulatory frameworks and technology security. In short, the aim is to perform an in-depth analysis of these factors and their effect on the national e-governance framework. This research offers empirical insights into the sociotechnical dynamics between Indian citizens and personal data related to e-governance projects. The collection and in-depth analysis of empirical case studies from actual settings, thorough surveys to measure awareness of the concern, and assessments of techniques used to protect privacy have the potential to contribute vastly to the achievement of our goal. Furthermore, the aim is to make concrete policy recommendations that guide implementing initiatives toward improving privacy in a digital governance scenario. This is a significant contribution to the scholarship on e-governance in India and its implications for individuals' privacy. It allows for the effective addressing of privacy issues and your suggested solutions. In all these ways, by unpacking these issues, the paper contributes to a more informed and productive conversation on the future of e-governance in India and its consequences for privacy.